Poverty Alleviation in the Ambidextrous Governance of Rural Communities - I Gusti Ayu Purnamawati; Putu Riesty Masdiantini; Nyoman Ari Surya Dharmawan; I Dewa Gede Anom Jambe Adnyana (Universitas Pendidikan Ganesha, 2025)
Poverty alleviation within an ambidextrous governance framework is a strategic approach that balances the optimization of existing programs with the exploration of new ideas and innovations to address the root causes of poverty more effectively and sustainably. This study aims to analyze how sustainable development can positively impact poor rural communities using variables such as community empowerment, intersectoral collaboration, integration of local cultural values, and poverty alleviation. This is a quantitative descriptive study conducted in Gunung Sari Village, Seririt District, Buleleng Regency, Bali Province. Data were collected using primary sources using a Likert-type questionnaire. Respondents included the village head, traditional village head, village institution managers, and community members, all of whom were within the village, resulting in a total sample of 105 individuals. Data were analyzed using Structural Equation Modeling with WarpPLS 5.0. The study's results, which utilized four independent variables, revealed differences between the findings and the hypothesis. The independent variables of community empowerment, intersectoral collaboration, and poverty alleviation had a positive and significant impact on sustainable development, whereas the integration of cultural values did not. cultural integration may be symbolic rather than functional. Although traditional values and community rituals are publicly recognized, they might not be formally institutionalized in governance, planning, or business models.